Sonogashira coupling reactions of bromomaleimides: route to alkyne/cis-Alkene/Alkyl maleimides: synthesis of luffarin X and cacospongionolide C - Deore, Prashant S.; N. P. Argade (Journal of Organic Chemistry, 2012)
Palladium-catalyzed Sonogashira coupling reaction of bromomaleimides with a diverse range of terminal alkynes has been demonstrated to furnish the corresponding alkynylmaleimides in very good yields. This coupling reaction followed by selective reduction of the triple bond to single bond have been utilized as the decisive steps to accomplish the first total synthesis of natural products (+/-)-luffarin X and (+/-)-cacospongionolide C.